Peningkatan Kapasitas Rentang Tegangan Uji Osiloskop Tipe Hm 203-7 dengan Pemanfaatan Alat Konverter - I Wayan Lastera (Program Studi Teknik Elektro UNUD, 2019)
Testing voltage regulation in power electronic practice, voltage capacity observed above 60 volt. The limited range capacity test voltage oscilloscope HM 203-7 type, testing can not be done properly. One of the approach that can be done to increase range capacity test voltage oscilloscope is use converter device. This study aim to know potency utilization of converter device on oscilloscope HM 203-7 type. The study was carried out by installing the converter device in the oscilloscope probe, the test voltage capacity being increased gradually. The results showed, converter device was able to increase range capacity test voltage oscilloscope HM 203-7 type to 240 Volt test voltage.